Enhancing the storage of mobile nodes through ad hoc storage as a service in MANETs. (7th January 2020) - Muralidhar, K.; Madhavi, K.
Summary: The data generation rate has grown explosively with the widespread use of mobile devices in several critical domains, including health care, education, and disaster recovery. This rapid increase in data volume is hindered by data storage restrictions on mobile devices. State‐of‐the‐art mobile computing platforms such as mobile cloud computing work towards providing indefinite storage space and augment mobile data storage by utilizing infinite cloud storage resources. Time Machine, iCloud, Dropbox, and other cloud‐oriented services facilitate the offloading of content. These services require uninterrupted internet connectivity. Low connectivity may induce system failure. Furthermore, network connectivity cannot always be ensured in rural areas and natural disaster–prone areas. In such cases, it would be more efficient for the originator to store a backup of the data in nearby mobile devices. Hence, users look for a storage/backup system in the vicinity. In this paper, we propose an efficient technique to obtain a temporary storage/backup service in areas with low network connectivity by using an ad hoc storage‐as‐a‐service method for mobile ad hoc networks (MANETs), with the help of nodes that provide temporary storage services to clients. Two types of nodes, namely, storage service providers (SSPs) and storage service requesters (SSRs), form the core of the proposed system. A set of SSRs accesses temporary storage from SSPs. Mobile clients can obtain a reliable storage service from this system. We use simulated experimental modules to analyze our model. We can also use this approach in a network‐disconnected area to demonstrate the practicality of providing a temporary storage service. Abstract : We identify the storage limitations of mobile devices, and most of the available cloud‐based storage/backup services are expensive. We propose an ad hoc mobile cloud, where each mobile can offload its data into the neighboring devices and use their unused storage resources, thereby offering an ad hoc storage as a service in MANETs. We model an efficient storage service provider (SSP) node selection strategy using the fuzzy logic. Further, we encrypt the information that will store on the SSP device to elude its access by unauthorized users. The proposed ad hoc storage as a service has application in disaster management, military operations, and mobile‐automated video surveillance applications.